2020
DOI: 10.3389/fphy.2020.583603
|View full text |Cite
|
Sign up to set email alerts
|

Network Coherence in a Family of Book Graphs

Abstract: In this paper, we study network coherence characterizing the consensus behaviors with additive noise in a family of book graphs. It is shown that the network coherence is determined by the eigenvalues of the Laplacian matrix. Using the topological structures of book graphs, we obtain recursive relationships for the Laplacian matrix and Laplacian eigenvalues and further derive exact expressions of the network coherence. Finally, we illustrate the robustness of network coherence under the graph parameters and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…J. Chen et al proposed graph operation method to construct the network models of book graph on the basis of star networks, and analyzed the influence of network internal parameters on its coherence. It is found that the more nodes in the star graph, the better the consensus of the book graph network [22]. D. Huang et al studied the Laplacian spectrum of several double-layer star-like networks, and analyzed and compared the coherence of these networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…J. Chen et al proposed graph operation method to construct the network models of book graph on the basis of star networks, and analyzed the influence of network internal parameters on its coherence. It is found that the more nodes in the star graph, the better the consensus of the book graph network [22]. D. Huang et al studied the Laplacian spectrum of several double-layer star-like networks, and analyzed and compared the coherence of these networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of network science, the research of complex networks has been extended to many fields, such as technical networks and transportation networks. Nowadays, the relevant theoretical knowledge of complex networks has been widely used in physics, computer science, life science, and other fields, such as consensus [1][2][3][4][5], resistance distance and Kirchhoff index [6], robustness [7,8], and network synchronization [9,10].…”
Section: Introductionmentioning
confidence: 99%